1997
DOI: 10.1088/0029-5515/37/7/i09
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of radiative mantle plasma power exhaust solutions for ITER

Abstract: ABSTRACT:The robustness of impurity-seeded radiative mantle solutions for ITER to uncertainties in several physics and operating parameters is examined. Our results indicate that -50 -90 % of the input power can be radiated h m inside the separatrix with Ne, Ar and Kr injection, without significant detriment to the core power balance or collapse of the edge temperature profile, for a wide range of conditions on the impurity pinch velocity, edge temperature pedestal, and plasma density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…6, where SOL radiation dropped as mantle radiation, and hence the SOL electron temperature, changed. Modeling has shown that krypton may be effective for impurity seeding in a reactor [15].…”
Section: Discussionmentioning
confidence: 99%
“…6, where SOL radiation dropped as mantle radiation, and hence the SOL electron temperature, changed. Modeling has shown that krypton may be effective for impurity seeding in a reactor [15].…”
Section: Discussionmentioning
confidence: 99%
“…(1). The application of impurities in fusion reactors will require detailed modelling, but calculations for ITER have demonstrated that solutions are possible with a high radiating fraction inside the LCFS [33]. In such scenarios, feedback control could be used to control impurity radiation but the minimum concentrations required to suppress ITG turbulence have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from other simulations with impurity seeding [8,9] in which the extrinsic impurities add to the intrinsic ones, the unique feature of our model consists in the selfconsistent interplay between the different impurities. In fact, each impurity affects the flux of the other impurities as well as the level of the power they radiate, due to changes each impurity causes in the local plasma density and temperature at the target, in the edge region and in the core.…”
Section: The Self-consistent Transport Model In Coredivmentioning
confidence: 99%
“…The problem of self-consistent modeling of the core and edge plasma has already been addressed in papers of Becker [9] and of Mandrekas/Stacey [8,12]. In our approach, for the plasma core we follow to a large extent the modeling assumptions in those papers, while a different model is used for the edge.…”
Section: The Self-consistent Transport Model In Coredivmentioning
confidence: 99%